Economic Globalisation and Human Rights : EIUC Studies on Human Rights and Democratization - Benedek, Wolfgang; De Feyter, Koen; Marrella, Fabrizio (Cambridge : Cambridge University Press, 2007)
Economic globalisation is one of the guiding paradigms of the twenty-first century. The challenge it implies for human rights is fundamental, and key questions have up to now received no satisfying answers. How can human rights protect human dignity when economic globalisation has an adverse impact on local living conditions? How should human rights evolve in response to a global economy in which non-statal actors are decisive forces? Economic Globalisation and Human Rights was originally published in 2007, and sets out to assess these and other questions to ensure that, as economic globalisation intensifies, human rights take up the central and crucial position that they deserve. Using a multidisciplinary methodology, leading scholars reflect on issues such as the need for global ethics, the localisation of human rights, the role of human rights in WTO law, and efforts to make international economic organisations more accountable and multinational corporations more socially responsible.
Title from publisher's bibliographic system (viewed on 02 May 2017).
Keywords: Human rights; Globalization